Didactic Cinquain as a Technique of Developing Critical Thinking in Teaching the Course “Culture of Speech and Expressive Reading” (Linguostylistic Studies, 2019)
The article interprets the terms cinquain, modern educational technology, the basic methodological principles of the educational technology based on the usage of critical thinking. High requirements to the professional training of students imply not only knowledge of the professional disciplines but also mastering the culture of speech. The abilities to communicate freely, affirm and convincingly prove that they your opinion are effective means in the formation of critical thinking.The study has employed fundamental theoretical methods to substantiate the main concepts of the article andto analyzethe methodical, linguistic, psychological and pedagogical literature. Synthesis and generalization of theoretical provisions made it possible to clarify the psychological and linguo-didactical principles of the concept culture of speech. Empirical methods have been applied to reveal the practical use of cinquain and evaluate the results of work with this technique.One of the most promising among the innovative educational strategies is critical thinking technology because its relevance is predetermined by the socio-cultural needs of modern life and corresponds to the concept of humanization of education. This method is based on the information analysis and enables the students to form their own judgments relying on the available facts and decide whether they are true or false. The study contributes to better understanding of the methods of developing the skills of speech culture and expressive reading of students and arouse interest to creative and non-standard aspects of their professional training. The application of critical thinking strategies at the lessons of speech culture allows to organize an independent activity of the students and develop their creative potential.The simplified form of the cinquain technique was first launched in the schools of the USA, and in the late 90s of the 20th century it was recommended in the post-Soviet educational process as one of the critical thinking development techniques. Sinquain should be used at all stages of developing culture of speech skills: forming communication competence (a plan for making up monologues and dialogues of various functional types), competence in reading (as a means to control awareness of what you read) and lexical competence (as a way of mastering the vocabulary); competence in writing. Key words: cinquain, innovation, linguistic culture, modern educational technology, modern high school. ReferencesBekh Ivan. “Personality: Two Scientific Views on Upbringing and Development”. Psychology and Personality, no 2, 2013, pp. 132–140.Dziamulych, Nataliia. “Senkan u systemi innovatsiinoho navchannia”. Pedahohichnyi poshuk, no 4, 2010, pp. 64–6.Innovatsiini tekhnolohii navchannia ukrainskoi movy i literatury. Ternopil: Aston, 2005.Kluster, Djevid. “Chto takoe kriticheskoe myshlenie?” Kriticheskoe myshlenie i novye vidy gramotnosti. Moskva: CGL, 2005, pp. 5–13.Kultura fakhovoho movlennia, edited by N. D. Babych. Chernivtsi: Knyhy-XXI, 2006.Ohneviuk, Viktor. Osvita v systemi tsinnostei staloho liudskoho rozvytku. Kyiv: Znannia Ukrainy, 2003.Pentyliuk, Mariia. Kultura movy i stylistyka. Kyiv: Vezha, 1994.Sovsun, Inna. Reforma vyshchoi osvity – tse ne vtorynne “sotsialne” chy “humanitarne” pytannia, a kliuchovyi politychnyi vyklyk dlia Ukrainy. nv.ua/ukr/opinion/ universitet-vilnikh-ljudej-2469362.html